Polymerase chain reaction for detection of measles virus in clinical samples. - Shimizu, H (1993)
A rapid and sensitive one-step reverse transcription polymerase chain reaction assay was developed to detect measles virus (MV) in nasal aspirates from patients with suspected MV infection. Oligonucleotide primers and probe were targeted to highly conserved regions of the matrix gene. Assay conditions were optimized to allow detection of as little as 1 PFU of an MV stock whose titer was known. Extraction of RNA from 38 nasal aspirates and then reverse transcription and MV matrix gene amplification yielded a polymerase chain reaction product of the predicted size in 14 of 14 MV culture-positive patients. Matrix gene amplification provides a rapid, sensitive, and specific supplementary assay to the currently available modalities for MV detection.